Predicting carnivore distribution and extirpation rate based on human impacts and productivity factors; assessment of the state of jaguar (Panthera onca) in Venezuela. (February 2017) - Jędrzejewski, Włodzimierz; Boede, Ernesto O.; Abarca, María; Sánchez-Mercado, Ada; Ferrer-Paris, José R.; Lampo, Margarita; Velásquez, Grisel; Carreño, Rafael; Viloria, Ángel L.; Hoogesteijn, Rafael; Robinson, Hugh S.; Stachowicz, Izabela; et al.
Abstract: The worldwide decline in carnivore populations has been attributed to various human impacts. However, our understanding of the mechanisms behind these declines is insufficient to predict the timing and location of local extinctions. We collected data on presence/absence and time since extirpation of jaguars across Venezuela. To test if human impacts or ecosystem productivity better explain the observed spatial variation in probability of jaguar occurrence we compared logistic regression models fit with different combinations of anthropogenic and environmental variables. Similarly, we modelled the time since extirpation, using a multiple regression approach. Our study supported the hypothesis that jaguar extirpations and distribution are determined by a joint effect of anthropogenic factors and environmental variables, mainly those related with ecosystem productivity. Human population density and habitat alterations exerted strong negative effects on jaguar populations, while annual precipitation, mean temperature, forest cover, primary productivity, and other vegetation indices had positive effects. The strength of human impact is shaped by ecosystem productivity: jaguars disappear faster in dry, unproductive areas, and survive better in humid, productive areas even when human densities are higher. We estimated that jaguars in Venezuela have been extirpated from approximately 26% of the territory of Venezuela; present jaguar range covers approximately 66% of the country. We demonstrate that human population density alone cannot adequately explain past extirpations nor predict future jaguar declines. We conclude that the predicted future growth of the human population will not necessarily determine jaguar declines, and proper management and conservation programs could potentially prevent jaguar extirpations. Highlights: Carnivores depend on joint effects of anthropogenic and environmental factors. Jaguars disappear faster in dry, unproductive areas. Chances of persistence are higher in humid and productive areas. Carnivore declines cannot be predicted from human density alone.